The Sirawu Sulo Tradition From A Cultural Accounting Perspective In The Village Of Pongka - Rais Abrar Syam; Muhammad Yamin; Lola Ramadhani; Nesa Usdayanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This qualitative case study examines the cultural accounting dimensions of the Sirawu Sulo tradition within its natural setting in Pongka Village, South Sulawesi. Grounded in direct field observations, semi structured interviews, and thematic analysis, the study explores how sacred intangible heritage operates beyond conventional market logic. The findings demonstrate that Sirawu Sulo embodies intrinsic qualitative values, including historical continuity, social cohesion, community identity, spiritual devotion, and preservation awareness, which cannot be captured through standard balance sheet asset recognition models. Forced financial capitalization risks distorting the sacred nature of communal traditions, whereas public sector accounting requires flexible nonmonetary disclosure mechanisms. By integrating narrative reporting, participatory community logging, and digital archiving into municipal accounting reports, public authorities can satisfy statutory accountability mandates while safeguarding indigenous autonomy. Ultimately, this research offers an integrative cultural accounting framework that bridges technical public financial management and intangible heritage conservation, advancing contemporary discourse on nonmarket social accountability and community based asset stewardship in rural agrarian societies.